(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Given that the rates of glaucoma-induced visual incapacitation are steadily increasing, predicting glaucomatous optic neuropathy is important. Purpose: To determine the diagnostic importance of the method proposed for the predicting the development and course of glaucomatous optic neuropathy in primary open-angle glaucoma (POAG) based on SweptSource-OCT-derived morphometric characteristics of the lamina cribrosa and daily intraocular pressure (IOP) in the clinical practice. Materials and Methods: Thirty patients were under observation. At baseline, the risk for the development of glaucomatous optic neuropathy in glaucoma suspects or the risk for disease progression in patients with already diagnosed POAG was assessed using our method. The latter is based on the determination of pressure exerted on the ganglion axons at the level of lamina cribrosa, given the specified IOP value and individual morphometric characteristics of the lamina cribrosa. Patients were divided into three groups depending on their risk levels. A DRI OCT Triton plus swept source OCT system (Topcon, Tokyo, Japan) was used to assess morphometric characteristics of the retina (ganglion cell complex thickness) and optic disc (lamina cribrosa thickness and diameter). The further course of the glaucomatous progression was studied using macular GCL++ characteristics. Results: At month 18, GCC thickness loss was statistically significantly larger in the moderate-risk group than in the low-risk group (p=0.001). In addition, it was statistically significantly larger in the high-risk group than in the low-risk group (p=0.00001) and in the moderate-risk group (p=0.00013). In the low-risk group, mean GCC thickness was 92.90±3.28 µm at baseline and 91.95±3.24 µm at month 18; however, the GCC thickness loss was not statistically significant (p=0.838). Conclusion: First, our method for predicting the development and progression of glaucomatous optic neuropathy in POAG based on SS-OCT-derived morphometric characteristics of the lamina cribrosa and daily IOP level enables determining the risk level of glaucomatous progression, which has been evidenced by the results of a prolonged observation. Second, significant macular GCC thinning was noted in 50% of cases of the high-risk group, even with a normal IOP level. Finally, introduction of the proposed method into clinical practice would enable planning effective glaucoma management aimed at prevention of optic nerve atrophy.